Polo-like kinase-1 as a novel target in neoplastic mast cells: demonstration of growth-inhibitory effects of small interfering RNA and the Polo-like kinase-1 targeting drug BI 2536 - Peter, B.; Gleixner, K. V.; Cerny-Reiterer, S.; Herrmann, H.; Winter, V.; Hadzijusufovic, E.; Ferenc, V.; Schuch, K.; Mirkina, I.; Horny, H.-P.; Pickl, W. F.; Mullauer, L.; et al. (Haematologica (Roma), 2011)
In advanced systemic mastocytosis the response of neoplastic mast cells to conventional drugs is poor and the prognosis is bad. Current research is, therefore, attempting to identify novel drug targets in neoplastic mast cells. Polo-like kinase-1 is a serine/threonine kinase that plays an essential role in mitosis and has recently been introduced as a new target in myeloid leukemias and solid tumors. In the present study, we analyzed the expression and function of Polo-like kinase-1 in neoplastic mast cells in systemic mastocytosis. As determined by immunostaining, primary neoplastic mast cells as well as the human mast cell leukemia cell line HMC-1 displayed phosphorylated Polo-like kinase-1. In addition, neoplastic mast cells expressed Polo-like kinase-1 mRNA. Polo-like kinase-1-specific small interfering RNA induced apoptosis in neoplastic mast cells, whereas no effect was seen with a control small interfering RNA. BI 2536, a drug targeting Polo-like kinase-1, was found to inhibit proliferation in HMC-1 cells in a dose-dependent manner. BI 2536 also inhibited the growth of primary neoplastic mast cells and cells of the canine mastocytoma cell line C2. The growth-inhibitory effects of BI 2536 on neoplastic mast cells were found to be associated with mitotic arrest and subsequent apoptosis. Finally, BI 2536 was found to synergize with the KIT-targeting kinase inhibitor midostaurin (PKC412) in inhibiting the growth of neoplastic mast cells. In control experiments, BI 2536 did not induce apoptosis in normal cultured mast cells. Collectively, our data show that Polo-like kinase-1 is a potential therapeutic target in neoplastic mast cells. Targeting Polo-like kinase-1 may be an attractive pharmacological concept in the management of advanced systemic mastocytosis.